Center-Pivot-Irrigated Short-Season Corn Cost-Return Budget - Dumler, Troy J.; Warmann, Gerald W. (My University, 1998)
Irrigated short season corn (or early-corn early) has gained acceptance in Kansas as an alternate crop to full season corn or grain sorghum.
MF1000_1998-10
Keywords: MF1000; Crops; MF